Bisazide cyanine dyes as fuorogenic probes for bis-cyclooctynylated peptide tags and as fluorogenic cross-linkers of cyclooctynylated proteins - Demeter, Orsolya; Köhler, Christine; Lemke, Edward A. (Bioconjugate chemistry, 2017)
Herein we present the synthesis and fluorogenic characterization of a series of double-quenched bisazide cyanine probes with emission maxima between 565 and 580 nm that can participate in covalent, two-point binding bioorthogonal tagging schemes in combination with bis-cyclooctynylated peptides. Compared to other fluorogenic cyanines, these double-quenched systems showed remarkable fluorescence intensity increase upon formation of cyclic dye-peptide conjugates. Furthermore, we also demonstrated that these bisazides are useful fluorogenic cross-linking platforms that are able to form a covalent linkage between monocyclooctynylated proteins.
Gesehen am 24.09.2018